An Application of Similarity Measure of Fuzzy Soft Sets in Verndor Selection Problem. (2018) - Singhal, Nisha; Verma, Ajay; Chouhan, Usha
Abstract: In so many real life problems we often interested to know whether two patterns or images are identical or approximately identical or at least to what degree they are identical. The similarity measure and distance measure both indicate the degree of similarity of two sets. At present, application of similarity measures in soft set theory and it's extensions for decision making in day to day life is progressing rapidly. The purpose of this paper is to introduce the concept of similarity between fuzzy soft sets based on the set-theoretic approach. A worthy application is also presented to select the most efficient vendor of raw materials for a company in a supply chain.